Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Tematik Pada Siswa Kelas IV SD - Sinta, Dwi Rahma; Resnani (JURIDIKDAS (Jurnal Riset Pendidikan Dasar), 2023)
The objective of this research was to find out the effect of jigsaw cooperative learning toward the 4th grade students’ thematic learning outcome in group XIX of elementary schools in Bengkulu City. This research was quantitative research. The method of this research was quasi experimental with the matching only pretest-posttest control group design. The populations of this research were all of the 4th grade of class B students in SDN 71 Bengkulu City with 32 students into experiment class and the 4th grade of class A students in SDN 72 Bengkulu City with 30 students into control class. There were two instruments were used, the knowledge outcome learning test from multiple choice which given through pretest and posttest, while skill and attitudes were given through observation sheets. The data analysis method was descriptive statistical analysis, prerequisite test analysis, and hypothesis test analysis. From the result of the calculation of t-test, t value was bigger than t table, with (4,89) >ttablel(1,67). The calculation of t value was higher than t table, it reveals that experiment class which used jigsaw cooperative learning could influenced the students’ learning outcome, it could be concluded that jigsaw cooperative learning influenced toward the 4th grade students’ thematic learning outcome in group XIX of elementary schools in Bengkulu City.